Multidrug‐resistant bacteria in diabetic foot infections: Experience from a portuguese tertiary centre. Issue 6 (21st August 2020) - Pessoa e Costa, Tomás; Duarte, Bruno; João, Ana Luísa; Coelho, Miguel; Formiga, Ana; Pinto, Margarida; Neves, José
Abstract: In recent years, the emergence of antibiotic resistant pathogens made increasingly difficult to establish appropriate empiric antimicrobial therapy protocols for acute diabetic foot infection (DFI) treatment. Early recognition of the population at‐risk for multidrug‐resistant (MDR) bacterial infection is of paramount importance in order to decrease large‐spectrum antibiotic overuse. This study used retrospective cohort study in a multidisciplinary tertiary diabetic foot unit. Patients with severe DFI were included and divided according to their infection resistance profile (susceptible vs MDR bacteria). Data regarding their comorbidities and length of hospital stay were collected. The primary endpoint was to determine the risk factors for MDR infections and to evaluate if these were associated with an increased length of stay (LOS). A total of 112 microbial isolates were included. Predominance of Gram‐positive bacteria was observed and 22.3% of isolated bacteria were MDR. Previous hospitalisation was associated with a higher likelihood of MDR infection. MDR bacterial infection was also associated with an increased LOS ( P = .0296). Our study showed a high incidence of MDR bacteria in patients with a DFI, especially in those who had a recent hospitalisation. MDR infections were associated with a prolonged LOS and represent a global public health issue for which emergent measures are needed.